Advances in Long-Acting Agents for the Treatment of HIV Infection - RANA, Aadia I. (Drugs, 2020)
Long-acting antiretroviral therapy (LA ART) holds the promise of new options for HIV treatment beyond the current paradigm of daily oral pills. Of particular interest is their potential role in addressing challenges with adherence to oral therapy and treatment fatigue. Similar to other conditions where long-acting formulations have proven effective such as contraception and mental health, LA ART could provide additional treatment choices to people living with HIV. This review provides an outline of the current landscape of LA ART for HIV treatment, both approved and under development, including cabotegravir, rilpivirine, leronlimab, islatravir, albuvirtide, GS-6207, and broadly neutralizaing antibodies. However, there are a number of research gaps for LA ART including issues regarding resistance and understudied populations, and this review highlights some of the challenges that will need to be addressed for clinical implementation of these novel treatment modalities.